2011
DOI: 10.1111/j.1464-410x.2011.10605.x
|View full text |Cite
|
Sign up to set email alerts
|

Among potent men post radical prostatectomy, does the need for phosphodiesterase inhibitors have an impact on sexual bother scores?

Abstract: OBJECTIVE To determine whether the current definition of potency, inclusive of phosphodiesterase inhibitor (PDEi) use, is valid with respect to sexual bother (SB). This will be assessed by characterizing the effect of PDEi use on SB scores in men who are potent post radical prostatectomy. PATIENTS AND METHODS The study population consisted of patients who were potent both before and after radical prostatectomy, with at least 2 years of follow-up. Disease-specific quality of life data were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…While a small portion of the decline may be attributed to increasing age and the natural progression of erectile dysfunction, it is unlikely that age would be the sole reason for this decline. Multiple sexual aids exist to improve sexual function and may alleviate bother [ 31 ]. Patients may benefit from education regarding these available and effective enhancement tools.…”
Section: Discussionmentioning
confidence: 99%
“…While a small portion of the decline may be attributed to increasing age and the natural progression of erectile dysfunction, it is unlikely that age would be the sole reason for this decline. Multiple sexual aids exist to improve sexual function and may alleviate bother [ 31 ]. Patients may benefit from education regarding these available and effective enhancement tools.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining nutrition and prostate cancer have yielded heterogeneous results, but the number of studies assessing the impact of nutrition on high-risk prostate cancer are limited [34]. One recent case-control study focused on aggressive prostate cancer found that a higher intake of well done, grilled, or barbequed red meat and its ensuing carcinogens (heterocyclic amines) could increase the risk of aggressive prostate cancer [35]. The link between nutrition and aggressive prostate cancer remains incompletely defined, and is a focus of ongoing studies.…”
Section: Obesity and Dietmentioning
confidence: 99%
“…É vasta a literatura sobre o impacto das doenças crônicas e seus tratamentos sobre a qualidade de vida (QV) e a função sexual de homens e mulheres. Podemos citar como exemplos estudos que investigaram a relação entre QV, satisfação sexual e doenças como depressão, insuficiência renal e câncer (Bertam & Castro, 2010;Nóra, Zambone & Facio Júnior, 2009;Rosen & cols., 2004); pesquisas que avaliam o impacto de tratamentos na QV, tais como a prostatectomia radical (Coelho & cols., 2003;Kamalov & cols., 2005;Punnen, Cooperberg, Sadetsky & Carroll, 2012;Van Andel & cols, 2004); ou ainda, estudos que avaliam as alterações da função sexual inerentes ao envelhecimento (Sousa, 2008;Viana & Madruga, 2008).…”
Section: Introductionunclassified